Simultaneous characterization and quantification of phenolic compounds in Thymus x citriodorus using a validated HPLC-UV and ESI- MS combined method - Pereira, Olívia R. (2013)
Thymus x citriodorus is a Lamiaceae plant extensively cultivated in Mediterranean region and used for centuries in culinary and in traditional medicine. The present work describes the detailed phenolic composition of T. x citriodorus for the first time, the by means of HPLC-DAD, ESI-MS and MSn and nuclear magnetic resonance (NMR) analyses. The ethanolic extract of T. x citriodorus was analyzed by reversed phase HPLC. The method of analysis was also validated concerning its linearity, instrumental and method precision (for repeatability, immediate precision and intermediate precision) and accuracy (absolute recovery study). The technique was combined with electrospray mass spectrometry in order to identify the phenolic compounds and the structure of the main phenolics was also confirmed by NMR analysis. The in-house validated HPLC-DAD method showed good linearity for the tested reference compounds as well as satisfactory repeatability and immediate precision values, for both instrument and method. Furthermore, the satisfactory results of intermediate precision analysis and recovery assays indicated that the chromatographic method could be used to quantify the main phenolic compounds of T. x citriodorus with adequate precision and accuracy. The extract was rich in rosmarinic acid (10.4±0.6 mg/g extract) that is a widespread phenolic acid in Thymus plants, but also in luteolin-7-O--glucuronide (12±2 mg/g extract), that was herein reported in Thymus for the first time. Other novel compounds comprised one eriodictyol dihexoside with O-glycosidic linkages, two eriodictyol-O-monohexosides, one quercetagetin dimethyl ether-O-hexoside, one naringenin-O-hexoside and chrysoeriol-7-β-O-glucoside. Having in mind the health-promoting properties reported in literature for some of the main polyphenols found in T. x citriodorus, we suggest that this plant has a high potential for being used as a functional food.